Respiratory health among professionals exposed to extreme SO2 levels from a volcanic eruption - Carlsen, Hanne Krage; Aspelund, Thor; Briem, Haraldur; Gislason, Thorarinn; Jóhannsson, Thorsteinn; Valdimarsdóttir, Unnur; Gudnason, Thorolfur (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVE ': 'The Holuhraun eruption of fall and winter 2014–15 produced large amounts of sulfur dioxide (SO2). The aim of this study was to determine if exposure to extreme SO2 levels affected the health of individuals working at the eruption site. ' ' METHODS ': 'During January‒March 2015, earth scientists, technicians, and law enforcement personnel who were about to work at the eruption site were invited to a respiratory health examination. Symptom reports and lung function measures, forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) were collected before and after an eruption site visit. Those with previous exposure (N=27) reported symptoms retrospectively. ' ' RESULTS ': 'Altogether, 41 individuals were invited to participate, 32 underwent a clinical examination at a hospital respiratory health clinic (baseline); 27 reported symptoms during earlier visits to the eruption site (retrospective symptom reports), 17 were re-examined 1–6 days after visiting the eruption site (follow-up). All participants’ lung function was within normal range both before and after exposure. At baseline, average FEV1 was 107.4% of predicted versus 106.6 at follow-up (P =0.82); average FVC was 107.0% of predicted at baseline versus 107.4% at follow-up (P=0.35). Eye and nasal irritation were more frequently reported during eruption site exposure by 24% versus 6% (P =0.37) for both. ' ' CONCLUSION ': 'Although “healthy-worker” effects cannot be excluded, our data indicate that SO2 exposure was associated with relatively mild and transient respiratory symptoms with no clinical signs of airway inflammation or airway obstruction.
Keywords: exposure; occupational exposure; respiratory health; SO2; sulfur dioxide; volcanic environment; volcanic eruption; volcanic gas